Optical properties of InxAl1-xAs alloy films - Yoon, J. J.; Ghong, T. H.; Byun, J. S.; Kim, Y. D.; Aspnes, D. E.; Kim, H. J.; Chang, Y. C.; Song, J. D. (AMER INST PHYSICS, 2008)
Pseudodielectric functions <epsilon > of InxAl1-xAs ternary alloy films were determined from 1.5 to 6.0 eV by spectroscopic ellipsometry. We minimized overlayer effects by performing wet-chemical etching to more accurately determine intrinsic bulk dielectric responses. Energies of the E-1, E-1+Delta(1), E-0', E-2, E-2+Delta(2) and E-2' critical points (CPs) were identified by band structure calculations of the linear augmented Slater-type orbital method. These calculations also showed a crossing of the E-0' and E-2 CP structures with increasing In composition and a new saddle point in the AlAs band structure. (C) 2008 American Institute of Physics.
Keywords: TEMPERATURE-DEPENDENCE; DIELECTRIC FUNCTION; PARAMETERS; GAAS; INP; INAS